Bunnell or cross-lock Bunnell suture for tendon repair? Defining the biomechanical role of suture pretension. Issue 1 (December 2015) - Jordan, Martin; Hoelscher-Doht, Stefanie; Fehske, Kai; Gilbert, Fabian; Jansen, Hendrik; Meffert, Rainer
Abstract Background Suture pretension during tendon repair is supposed to increase the resistance to gap formation. However, its effects on the Bunnell suture technique are unknown. The purpose of this study was to determine the biomechanical effects of suture pretension on the Bunnell and cross-lock Bunnell techniques for tendon repair. Methods Eighty porcine hindlimb tendons were randomly assigned to four different tendon repair groups: those repaired with or without suture pretension using either a simple Bunnell or cross-lock Bunnell technique. Pretension was applied as a 10 % shortening of the sutured tendon. After measuring the cross-sectional diameter at the repair site, static and cyclic biomechanical tests were conducted to evaluate the initial and 5-mm gap formation forces, elongation during cyclic loading, maximum tensile strength, and mode of failure. The suture failure mechanism was also separately assessed fluoroscopically in two tendons that were repaired with steel wire. Results Suture pretension was accompanied by a 10 to 15 % increase in the tendon diameter at the repair site. Therefore, suture pretension with the Bunnell and cross-lock Bunnell repair techniques noticeably increased the resistance to initial gap formation and 5-mm gap formation. The tension-free cross-lock Bunnell repair demonstrated more resistance to initial and 5-mm gap formation, less elongation, and higher maximum tensile strength than the tension-free Bunnell repair technique. The only difference between the tensioned cross-lock Bunnell and tensioned Bunnell techniques was a larger resistance to 5-mm gap formation with the cross-lock Bunnell technique. Use of the simple instead of cross-lock suture configuration led to failure by suture cut out, as demonstrated fluoroscopically. Conclusion Based on these results, suture pretension decreases gapping and elongation after tendon repair, and those effects are stronger when using a cross-lock, rather than a regular Bunnell suture. However, pretension causes an unfavorable increase in the tendon diameter at the repair site, which may adversely affect wound healing.